Lékové formy vinanu zolpidemu - Gruberová, Lucie; Kratochvíl, Bohumil (Chemické listy, 2018)
Insomnia is one of the long-term problems that afflict a major part of the population. The high incidence of the disorder and its health consequences are alarming. In the medical treatment of insomnia, z-hypnotics, especially zolpidem, are most used. Drug zolpidem as a selective agonist has a high affinity for α1 subunit of the GABAA receptor. Only zolpidem tartrate is used for the formulation of dosage forms. In the US, a number of zolpidem dosage forms have become available. These novel dosage forms enhance the pharmacokinetic profile of oral immediate release tablets and facilitate the administration. Among them, there are oral controlled release tablets, sublingual tablets, orally dispersible tablets and oral spray. The development of alternative dosage forms increases the therapeutic options available to patients.
Keywords: lékové formy; zolpidem; Zolpidem; Dosage Forms; hypnotika a sedativa; Hypnotics and Sedatives